Eventos carcelarios : Subjetivación política e imaginario revolucionario en América Latina - Pous, Federico (Book collections on Project MUSE., 2022)
"This book investigates the experience of political prisoners under dictatorial regimes in Paraguay, Brazil and Argentina during the second part of the 20th century. The analysis illuminates certain unique events that occurred in the dungeons of the dictatorship, such as escapes and liberations, to think about the impact of the revolutionary imaginary in the construction of political subjectivity, narratives about leftist militancy and historical memory. These prison events marked the moment of greatest strength and greatest weakness of the revolutionary project: on the one hand, they challenged and outwitted ferocious dictatorships, and on the other, they exposed the political fantasies of the left that preceded the subsequent catastrophic defeat. The reading hypothesis is that the distance between the great revolutionary event, which never took place, and these singular events that seemed to "confirm" its arrival, has been inserted as a modus operandi of political subjectivation, disarticulating the horizon of contemporary radical transformation"--